2016
DOI: 10.3402/jchimp.v6.33299
|View full text |Cite
|
Sign up to set email alerts
|

The changing anatomic position of squamous cell carcinoma of the lung – a new conundrum

Abstract: BackgroundTraditionally, squamous cell carcinoma (SCC) of the lung is a central rather than a peripheral form of lung cancer. Rates of SCC in the lung periphery are typically sited in the 15–30% range. Recently, we observed that a significant portion of newly diagnosed SCC was located on a periphery. A comprehensive review of the tumor data at our facility, a busy teaching hospital with a large cohort of cancer patients, was undertaken to assess whether there had been a substantive change in the traditional ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…It is well known fact that localization of SCC is predominantly central and about one third of SCC are peripherally located. [ 21 ] However, incidence of peripheral SCC seems to be increasing and referring to recent reports, peripheral SCC is reported up to 40% to 55% of all lung SCC [ 22 24 ] in correlation with our study.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known fact that localization of SCC is predominantly central and about one third of SCC are peripherally located. [ 21 ] However, incidence of peripheral SCC seems to be increasing and referring to recent reports, peripheral SCC is reported up to 40% to 55% of all lung SCC [ 22 24 ] in correlation with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Squamous cell carcinoma (SCC) used to be a representative histological type of centrally-located lung cancer, but recent studies have reported an increase in peripherally-located SCCs. The incidence of peripherally-located SCCs, which was 15-30% around 25 years ago (5,6), increased to nearly 50% of diagnosed or resected SCC cases (7). Previous reports have revealed a difference in clinicopathological features between central-type and peripheral-type SCCs (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the incidence of central of SQCC is well known in many studies including Mizushima et al [15] who found in their study over 235 squamous cell carcinomas that 129 was peripheral and 106 were central and William Krimsky et al [16] found a total of 56 patients were diagnosed with SCC. Of these, 55% (n = 31) had peripheral and 45% (n = 25) had central SCC.…”
Section: Discussionmentioning
confidence: 99%